DEVELOPING AN INTELLIGENT ASSISTANT EMBEDDED IN A SMART MIRROR PROTOTYPE - Hui, Chen Hao (Universiti Malaysia Sarawak, (UNIMAS), 2020)
A mirror is a very important tool in our daily life. We spend a decent amount of time every day to stand in front of a mirror, whether it is to put on makeup, set a hairstyle or adjust outfit. However, we are unable to check our phone for news and weather when we are adjusting our looks in front of the mirror. In a busy daily schedule, it would be time-consuming to do both consecutively. Therefore, efficiency and productivity will be lowered. The purpose of this project is to explore and search for a possible solution to the problem statement. This project is the development of an intelligent personal assistant embedded in a Smart Mirror prototype. The prototype can reflect the image of the users like a normal mirror while displaying various information on the mirror. Users can carry voice interaction with the system. In this way, the users can interact with the system while getting themselves ready for the day. As a result, there will be an increase in the efficiency and productivity of users.